2021
DOI: 10.1177/1403494821993725
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the treatment of injuries during lockdown in Norway

Abstract: Aims: In order to prevent a major outbreak of COVID-19 disease in Norway, a series of lockdown measures was announced on 12 March 2020. The aim of the present paper was to describe the impact of this lockdown on the treatment of injuries. Methods: We collected hospital data on injury diagnoses from a national emergency preparedness register established during the pandemic. We identified the number of injured patients per day in the period 1 January–30 June 2020, and analysed the change in patient volumes over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…A nationwide study from Norway compared all injuries from a national registry of emergencies in the 3 weeks of lockdown to three prior weeks in 2020 and found a 43.4% reduction in overall admissions. 26 Our numerical but not statistically significant reduction in trauma admissions in the first month of lockdown was smaller than at other major trauma centers. The absolute decrease of trauma patients (7.5 patients) and traffic injuries combined (10.5 patients) were limited and therefore hampers interpretation.…”
Section: Discussioncontrasting
confidence: 54%
“…A nationwide study from Norway compared all injuries from a national registry of emergencies in the 3 weeks of lockdown to three prior weeks in 2020 and found a 43.4% reduction in overall admissions. 26 Our numerical but not statistically significant reduction in trauma admissions in the first month of lockdown was smaller than at other major trauma centers. The absolute decrease of trauma patients (7.5 patients) and traffic injuries combined (10.5 patients) were limited and therefore hampers interpretation.…”
Section: Discussioncontrasting
confidence: 54%
“…demonstrated that for a similar time period, the overall number of patients undergoing surgery for musculoskeletal trauma in Scotland decreased during the first lockdown. 16 An overall reduction in musculoskeletal injuries requiring operative intervention during lockdown was also observed in France, 17 and Norway 18 during this time period. Therefore, the increase in hospital admissions from cycling injuries likely reflects the higher numbers of patients requiring operative strategies for their injuries over conservative management.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, a Portuguese and Netherlands study showed similar findings where the upper limb had a higher frequency of injury location [22,25]. Seeking medical interventions for injuries during quarantine became significantly low (22.9%) compared to the time before the quarantine (45.5%), an overall reduction of 22.6% between the 2 periods, which might be due to the strict COVID-19 regulation of emergency departments and surgical units that required adaptation of the spaces and emergency rooms that impacted the maximum capacity of the medical centers or due to the decrease in the number of injuries [26,27]. Similarly, in Brazil, an epidemiological study related to CrossFit athletes showed similar findings in which 42.0% of participants who get injured reported seeking a health care professional to diagnose or treat an injury [28].…”
Section: Discussionmentioning
confidence: 99%